The Effect of Tax Understanding, Service Digitalization and Service Quality on Increasing Tax Compliance with Volunteers as a Moderation Variable - Berkah Rahmawati; Lince Bulutoding; Della Fadhilatunisa (Academic Bright Collaboration, 2025)
This study aims to analyze the influence of tax understanding, service digitization, and service quality on individual taxpayer compliance, with tax volunteers as a moderation variable. This study uses a quantitative approach with a data collection technique in the form of distributing questionnaires to 110 taxpayers registered at the Sungguminasa Tax Counseling and Consulting Service Office (KP2KP). Data were analyzed using multiple linear regression tests and Moderated Regression Analysis (MRA) analysis. The results of the study show that simultaneously and partially, tax understanding, digitization of services, and quality of service have a significant influence on tax compliance. The variable of tax volunteers strengthens the influence of understanding and digitization of services on tax compliance, but weakens the influence of service quality. This research shows that tax volunteers play the role of pure moderators.